The Effect of Salbutamol and Budesonide Pediatric Doses on Dental Enamel and Packable and Flowable Composites: Microhardness, Surface Roughness and Color - Maria Salem Ibrahim; Fatimah Mohammed Alatiyyah; Khawla Abbas Mohammed; Hibah Nouh Alhawaj; Abdulrahman A. Balhaddad; Ahmed Salem Ibrahim (MDPI AG, 2023)
Objective: To assess and compare the effects of two pediatric anti-asthmatic medication doses on the microhardness of enamel and microhardness, surface roughness and color of restorative materials. Methods: Human enamel samples and packable and flowable composite restorations were used. The samples were exposed to Salbutamol (0.6 mL/6 mL saline) and Budesonide (2 mL/2 mL saline) via a custom-made chamber connected to a nebulizer. Medication administration was conducted for 10 days. The samples were brushed with an electronic brush in a continuous and circular mode for 10 s after 10 min of medication administration. Assessments of microhardness, surface roughness and color were carried out at three different time intervals: baseline (T0), 5 days (T1) and 10 days (T2). One-way analysis of variance (ANOVA), a two-sample t-test and a Bonferroni multiple comparison test were used to analyze the data and compare between the groups. Results: Both medications significantly (p < 0.05) decreased the microhardness of the enamel and composite samples after 10 days. Both medications lowered the surface roughness of both types of composite with a greater effect observed after 10 days of Budesonide administration (p < 0.05). Both medications had comparable detectable color change on both types of composite with a greater effect observed after 10 days of Budesonide administration (p < 0.05). Conclusion: Salbutamol and Budesonide significantly decreased microhardness in the enamel samples. Both medications affected the properties of packable and flowable composites. The packable composite showed more resistance to microhardness changes. Both medications showed a clinically detectable change in the color of packable and flowable composites.